2022
DOI: 10.1002/nag.3413
|View full text |Cite
|
Sign up to set email alerts
|

Influence of coupling effect in the chemo‐hydro‐mechanical consolidation of saturated soil layer

Abstract: In geological sites containing chemical pollutants, the clay buffer layer (CBL) is frequently utilized to isolate the pollutants from the external environment. Moreover, hydraulics, mechanics, and chemistry jointly pose impacts on the consolidation of CBL and the diffusion of chemical substances. In order to consider the coupled effect (termed chemo-hydro-mechanical-CHM), a one-dimensional consolidation model that fully considers CHM coupling (such as convection, ultrafiltration, and osmotic efficiency) is est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 28 publications
(54 reference statements)
0
17
0
Order By: Relevance
“…Zheng et al 52 investigated the 1D CHM model in an elastic soil and discussed the influence of coupling effect. By applying η = 0, the model presented in this study is simplified to the simplified CHM model of elastic soil.…”
Section: Degradation Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Zheng et al 52 investigated the 1D CHM model in an elastic soil and discussed the influence of coupling effect. By applying η = 0, the model presented in this study is simplified to the simplified CHM model of elastic soil.…”
Section: Degradation Modelmentioning
confidence: 99%
“…By applying η = 0, the model presented in this study is simplified to the simplified CHM model of elastic soil. The physical parameters used in Zheng et al 52 are listed in Table 1. The excess pore-fluid pressure, solute concentration, and displacement obtained via these parameters were compared with those in Zheng et al 52 The result is shown in Figure 2.…”
Section: Degradation Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, the Laplace transform is more commonly used to solve the model of well hydraulics for both CRR and CHR tests. 21,[27][28][29][35][36][37][38][39] However, the transform from the physical domain to the Laplace domain can be rather difficult or even impossible because of the including temporally variable permeability function. For this reason, the Hankel transform with the v-th order was applied with respect to 𝑟 ′ for the case of CRR.…”
Section: Approximate Analytical Solutionsmentioning
confidence: 99%